CLINICAL AND PARACLINICAL CHARACTERISTICS OF WOMEN SCREENED FOR CERVICAL CANCER AT HANOI CANCER HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Describe some clinical and paraclinical characteristics of women screened for cervical cancer  at Hanoi Oncology Hospital during the period 2024-2025. Subjects and Methods: A retrospective and prospective cross-sectional study of 339 women aged 21-65 who had been sexually active and screened for cervical cancer  at Hanoi Oncology Hospital from October 2024 to December 2025. The participants in the study gynecological examination, VIA, PAP smear, collected the characteristics of the object of study population sociology. Results: The mean age was 43,4 ± 8,2 years, the 40-49 age group accounted for the highest percentage at 44,2%. The group with 1–2 pregnancies accounted for the highest percentage at 70,2%, followed by 3 or more pregnancies at 24,2%; the percentage of patients with a history of miscarriage was 13,3%; and the percentage of those who underwent abortion was 57,8%. The majority of study participants were still menstruating (76,7%); the average age of first sexual intercourse was 23,1 ± 2,9; and the majority of study participants had one sexual partner (88,2%). Vaginal discharge was the most common reason for seeking medical attention (38,1%). The rate of benign cervical lesions was 75,8%, normal lesions accounted for 20,9%, and abnormalities accounted for 3,3%. The rates of VIA-positive and HPV-positive results in the study were 11,8% and 19,2%. 8,3% of the subjects had abnormal Pap test results. Conclusion: Women undergoing cervical cancer screening at Hanoi Oncology Hospital during the 2024-2025 period were mainly aged 40-49. Cervical lesions are predominantly benign, accounting for 75.8% and the rates of positive VIA, HPV, and Pap test results in the study were 11,8%, 19,2%, and 8,3%.
Keywords: Cervical cancer screening, HPV, PAP, VIA.